Metabolic characterization of primary rat hepatocytes cultivated in parallel microfluidic biochips. Issue 9 (19th February 2013) - Legendre, Audrey; Baudoin, Régis; Alberto, Giulia; Paullier, Patrick; Naudot, Marie; Bricks, Thibault; Brocheton, Jessy; Jacques, Sébastien; Cotton, JérôME; Leclerc, Eric; Nakashima, Emi; Brouwer, Kim; et al.
Abstract The functionality of primary rat hepatocytes was assessed in an Integrated Dynamic Cell Cultures in Microsystem (IDCCM) device. We characterized the hepatocytes over 96 h of culture and evaluated the impact of dynamic cell culture on their viability, inducibility, and metabolic activity. Reverse Transcription quantitative Polymerase Chain Reaction (RTqPCR) was performed on selected genes: liver transcription factors (HNF4α and CEBP), nuclear receptors sensitive to xenobiotics (AhR, PXR, CAR, and FXR), cytochromes P450 (CYPs) (1A2, 3A2, 3A23/3A1, 7A1, 2B1, 2C6, 2C, 2D1, 2D2, and 2E1), phase II metabolism enzymes (GSTA2, SULT1A1, and UGT1A6), ABC transporters (ABCB1b and ABCC2), and oxidative stress related enzymes (HMOX1 and NQO1). Microperfused‐cultured hepatocytes remained viable and differentiated with in vivo‐like phenotype and genotype. In contrast with postadhesion gene levels, the first 48 h of perfusion enhanced the expression of xenosensors and their target CYPs. Furthermore, CYP3A1, CYP2B1, GSTA2, SULT1A1, UGT1A1, ABCB1b, and ABCC2 were upregulated in IDCCM and reached above postextraction levels all along the duration of culture. Metabolic activities were also confirmed with the detection of metabolism rate and induced mRNAs after exposure to several inducers: 3‐methylcholanthrene, caffeine, phenacetin, paracetamol, , and midazolam. Finally, this metabolic characterization confirms that IDCCM is able to maintain rat hepatocytes functions to investigate drug metabolism. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3264–3276, 2013